The relationship between diabetes mellitus, periodontal health status and dental caries - Faisal, Ghasak Ghazi; Hilal Abbood Al-Bayati, Lina; Ramli, Nur Izzati Najwa; Syed Mohamad Nadzir Alkaff, Syarifah Nur Izzati Alkaff (2015)
Objectives: To study the relationship between diabetes mellitus, periodontal health status and dental caries. Materials and methods: A case-control study involving 42 type II diabetic patients and 42 non-diabetic patients was conducted at Polyclinic, Kulliyyah of Dentistry, International Islamic University Malaysia. Their decay, missing, filling, total scores (DMFT) and full mouth periodontal parameters were recorded. Patients’ sociodemographic background was obtained and diabetic profile was assessed. Results: The percentage of diabetic patients that were diagnosed with periodontitis was 88.1% compared to 59.5% in the control group and it was statistically significant (p<0.05). In comparing periodontitis in both groups, the bleeding on probing (BOP) and pocket depth (PD) showed no significant difference (p>0.05) while the clinical attachment loss (CAL) showed significant difference (p<0.05). The mean values for decay, missing and filled teeth in the diabetic group were 2.24(±1.94), 8.52(±6.13) and 3.76(±2.79) respectively, while in the control group were 1.83(±1.92), 4.79(±3.8) and 2.79(±2.76) respectively. Among all three mean values, missing teeth was the only one that showed significant difference (p<0.05). However, the total DMFT score between the two groups showed statistically significant results (p<0.05). Among the diabetic patients, there was no significant difference between those with high random blood glucose level and those with normal level in terms of the periodontal parameters and DMFT. Conclusions: Diabetes mellitus negatively affects oral health as reflected by the higher DMFT scores in diabetic patients. There was also a greater prevalence and severity of periodontitis in diabetic subjects than in nondiabetics.